(untitled) (The Batuk, 2021)
This paper aims to examine the impact of five commonly used dividend determinants as; net profit, cash flow, size, market to book value, and slack on the dividend payout ratio of 19 Nepalese commercial banks. This study uses secondary data collected from annual financial statements of the banks listed on the Nepal Stock Exchange. A total of 95 observations of the variables five fiscal years are considered. The method used casual comparative research design and regression analysis is conducted. The results showed a positive and significant effect of two variables; market to book value and slack on dividend payout ratio. The result also showed the positive effect of size on the dividend payout ratio. However, the results indicated a negative effect of profitability and cash flows on the dividend payout ratio of the banks.